Internet Branding In Malaysia - Yann, Wong Hur (2004)
An exploratory study on Internet branding landscape in an emerging market like Malaysia, this paper presents empirical evidence of the development of Internet brands in Malaysia, as well as the online consumers' perceptions and attitudes in the country.